Ayurvedic Insights on Linkage Between Grivastambha (Cervical Spondylosis) to Patient Outcomes: A Statistical Analysis of Personalized Data (International Journal of Ayurveda and Pharma Research, 2024)
Disease can be traced back for its manifestation since antiquity, just with development of mankind. Day by day, advancement in medical science is approaching diseases with utmost treatment and diagnostic applications. Though, before starting treatment- nature of disease, course of disease, causative factors etc, should be kept in mind to understand and eradicate disease from its root. Patients’ detail history including habit, activity etc. can help to understand his/her health status, disease condition and prognosis. Here, subjects of Grivastambha (cervical spondylosis), one of the Vataja Nanatmaja Vikara (Vata Doshika disease) are taken and observed for their personalized data to link with disease pathogenesis, which can further be used for effective prevention and treatment policies in future. This study shows the application, interpretation of data individually and relatively.